Cancer patients' desire for psychological support: prevalence and implications for screening patients' psychological needs - Isabelle Merckaert; Yves Libert; Sophie Messin; M. Milani; Jean‐Louis Slachmuylder; Darius Razavi (2009)
To investigate cancer patients' desire for psychological support and to identify patients' sociodemographic, disease-related and psychological factors associated with this desire.The study is part of a multicenter, cross-sectional study assessing cancer patients' needs and desire for psychological support. Patients completed the Hospital Anxiety and Depression Scale, the Ways of Coping Checklist, the Cancer Rehabilitation Evaluation System and reported their desire for psychological support.Among the 381 included patients, women (26%) desired psychological support significantly more often than men (11%) (p<0.001). Patients' desire for psychological support was associated with being younger (OR=0.94; p<0.001 for women and OR=0.93; p=0.007 for men) and having a support-seeking coping (OR=1.10; p=0.010 for women and OR=1.36; p=0.003 for men). Other contextual factors such as difficulties encountered and treatment modalities were diversely associated with women and men's desire for psychological support. Neither women's, nor men's psychological distress was associated with their desire for psychological support.One female cancer patient out of four and one male cancer patient out of ten desire psychological support. Results emphasize the need to screen not only for cancer patients' distress but also for their desire for psychological support. This will allow implementing psychological interventions according to patients' needs and desire.